Electrochemical Investigation on the Interaction Between Colchicine and DNA - Xu, Hui; Hou, Faju; Zhang, Xiaoning (Current Physical Chemistry, 2011)
The electrochemical behavior of the interaction of colchicines (COLC) and calf thymus DNA was investigated by differential pulse voltammetry (DPV). After the addition of the single-stranded DNA (ssDNA) or doublestranded DNA (dsDNA), the peak current of COLC declines and the peak potential shifts differently for ssDNA and dsDNA. The experimental results show that a complex is formed due to the interaction of COLC and DNA, and that different binding modes exist between COLC and dsDNA or ssDNA. COLC interacted more strongly with dsDNA than with ssDNA, by which dsDNA and ssDNA could be distinguished. The binding site m and the binding constant β of COLC to dsDNA were 2.0±0.2 and (3.7±0.5)x108 M-1, respectively. The peak current shows a linear relationship with the DNA concentration in the range of 100 220 μg/L, and the linear regression equation is Ip(10-6A) = -1.40 CdsDNA (mg/L) + 1.49 (R = 0.9975) with the correlation coefficient of 0.9975. This method exhibits a good recovery and sensitivity,which could be applied to the determination of DNA in sample.
Keywords: DNA?drug interactions